Apocarotenoids as Stress Signaling Molecules in Plants - Maurizio Carnà; Paolo Korwin Krukowski; Edoardo Tosato; Stefano D’Alessandro (Agriculture)
Apocarotenoids are ancient signaling molecules that have played crucial roles in biological communication and adaptation across evolutionary history. Originating in cyanobacteria, these molecules have diversified significantly in plants, where they contribute to stress perception, developmental regulation, and environmental responses. While some apocarotenoids, such as abscisic acid (ABA) and strigolactones (SLs), have been formally classified as plant hormones due to the identification of specific receptors, many others remain functionally enigmatic despite their profound effects on gene regulation and plant physiology. In this study, we focus on β-carotene-derived apocarotenoids that lack identified receptors, shedding light on their potential signaling roles beyond traditional hormone pathways. By synthesizing current knowledge, we highlight key gaps in understanding their biosynthesis, transport, perception, and downstream effects. Addressing these gaps is essential for unraveling the full scope of apocarotenoid-mediated signaling networks in plants. A deeper understanding of these molecules could not only redefine plant hormone classification but also open new avenues for improving crop resilience and stress adaptation in the face of climate change.